BOMBAY DUCK FISHERY OF MAHARASHTRA WITH SPECIAL REFERENCE TO VBRSOVA - Bapat, S V; Alawani, S A (Indian Journal of Fisheries, 2011)
The Bombay duck fishery, confined mainly to Maharashtra and Gujarat, is supportedby a single species, Harpodon nehereus. The annual landings averaged about11,000 tonnes in early fifties, and rose to over 100,000 tonnes in late fifties but stabilisedaround 80,000 tonnes (forming about 10% of the annual marine fish catch of the country)from 1964 onwards. The Maharashtra catch stabilised around 30,000 tonnes inearly sixties and the Gujarat catch around 50,000 tonnes in late sixties